Digital contact tracing and exposure notification: ethical guidance for trustworthy pandemic management - Ranisch, Robert; Nijsingh, Niels; Ballantyne, Angela; Van Bergen, Anne; Buyx, Alena; Friedrich, Orsolya; Hendl, Tereza; Marckmann, Georg; Munthe, Christian; Wild, Verina (Ethics and Information Technology, 2021)
There is growing interest in contact tracing apps (CT apps) for pandemic management. It is crucial to consider ethical requirements before, while, and after implementing such apps. In this paper, we illustrate the complexity and multiplicity of the ethical considerations by presenting an ethical framework for a responsible design and implementation of CT apps. Using this framework as a starting point, we briefly highlight the interconnection of social and political contexts, available measures of pandemic management, and a multi-layer assessment of CT apps. We will discuss some trade-offs that arise from this perspective. We then suggest that public trust is of major importance for population uptake of contact tracing apps. Hasty, ill-prepared or badly communicated implementations of CT apps will likely undermine public trust, and as such, risk impeding general effectiveness.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Contact tracing apps; Covid-19; Health apps; mHealth; Public health; Public trust